2015
DOI: 10.3390/v7092860
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Therapeutic Treatments and Screening Strategies for the Prevention and Treatment of HPV-Associated Head and Neck Cancer

Abstract: The rise in human papillomavirus (HPV)-associated head and neck squamous cell carcinoma (HNSCC) has elicited significant interest in the role of high-risk HPV in tumorigenesis. Because patients with HPV-positive HNSCC have better prognoses than do their HPV-negative counterparts, current therapeutic strategies for HPV+ HNSCC are increasingly considered to be overly aggressive, highlighting a need for customized treatment guidelines for this cohort. Additional issues include the unmet need for a reliable screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 164 publications
(901 reference statements)
0
34
0
Order By: Relevance
“…They primary source (41% of cases) is the oral cavity, but they are also often found in the pharynx and larynx, (22 and 24% of cases, respectively) (2). The majority of patients with HNSCC are clinically identified prior to metastasis, and therefore are potentially able to be cured by an aggressive therapy regimen, comprising surgery, chemotherapy and/or radiotherapy (3). Nevertheless, despite recent improvements to utilized surgical techniques, chemotherapy and radiation delivery, and supportive care, which have improved the quality of life of patients, the HNSCC disease recurrence rate remains unacceptably high, occurring in up to 50% of patients within the first 2 years of diagnosis (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…They primary source (41% of cases) is the oral cavity, but they are also often found in the pharynx and larynx, (22 and 24% of cases, respectively) (2). The majority of patients with HNSCC are clinically identified prior to metastasis, and therefore are potentially able to be cured by an aggressive therapy regimen, comprising surgery, chemotherapy and/or radiotherapy (3). Nevertheless, despite recent improvements to utilized surgical techniques, chemotherapy and radiation delivery, and supportive care, which have improved the quality of life of patients, the HNSCC disease recurrence rate remains unacceptably high, occurring in up to 50% of patients within the first 2 years of diagnosis (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to HPV-positive HNSCC patients, which have a more favorable prognosis (3,4), patients with HPV-negative HNSCC have a poor prognosis, with more than half of the patients developing recurrent or metastatic diseases (5). Recently, checkpoint inhibitors, such as mAbs against programmed death-1 receptor (PD-1) and its ligand (PD-L1), have shown promising therapeutic efficacy in both HPV-positive and -negative HNSCC (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…HPV-associated tumours tend to occur in young (< 60 years age), male, Caucasian patients, typically with a higher level of education and income, as well as improved functional status [2,5,7,8]. This cohort of patients tends to present at an earlier T-stage, and a more advanced N-stage at diagnosis; and several large trials have demonstrated an improved responsiveness to chemotherapy and radiotherapy primarily, as well as an overall improved survival rate [5,7,8].…”
Section: Doi: 101159/000489786mentioning
confidence: 99%
“…HPV are non-enveloped, double-stranded DNA viruses of the Papillomaviridae family, with a genome of approximately 8,000 bp [2,12]. The mucosal HPV genome encodes 6 early proteins (E1-2 and E4-7) and 2 late structural proteins (L1, L2), and a non-coding control region [11].…”
Section: Human Papillomavirusmentioning
confidence: 99%
See 1 more Smart Citation